2014
DOI: 10.1177/1557988314549413
|View full text |Cite
|
Sign up to set email alerts
|

Supporting and Sharing—Home Birth

Abstract: The planned home birth has provoked discussion around the world. Home birth has been described as a positive experience, but results regarding the safety of home birth are controversial. To date, the phenomenon has mainly been examined from the mother's point of view, and there is only one previous study reporting fathers' perspective. The purpose of the present phenomenological qualitative interview study was to investigate fathers' experiences of planned home birth. Eleven fathers were interviewed, and the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
6
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 24 publications
4
6
0
2
Order By: Relevance
“…In fact, most of them initially had no firm views about the impending birth and would not have raised the idea of going outside conventional care themselves. This is in line with other studies [18][19][20]22,33], where the pregnant woman initiated conversations about birth options that were against convention or medical recommendation. Often these plans originated in a previous traumatic experience in maternity care, where the women experienced a cascade of interventions and lack of shared decision making [18,20,24,28].…”
Section: The Women Take the Lead And Filter Informationsupporting
confidence: 89%
See 4 more Smart Citations
“…In fact, most of them initially had no firm views about the impending birth and would not have raised the idea of going outside conventional care themselves. This is in line with other studies [18][19][20]22,33], where the pregnant woman initiated conversations about birth options that were against convention or medical recommendation. Often these plans originated in a previous traumatic experience in maternity care, where the women experienced a cascade of interventions and lack of shared decision making [18,20,24,28].…”
Section: The Women Take the Lead And Filter Informationsupporting
confidence: 89%
“…This is in line with other studies [18][19][20]22,33], where the pregnant woman initiated conversations about birth options that were against convention or medical recommendation. Often these plans originated in a previous traumatic experience in maternity care, where the women experienced a cascade of interventions and lack of shared decision making [18,20,24,28]. The overarching theme of 'fear' (of unnecessary intervention, loss of autonomy, provider's fear of bad outcome and legal ramifications) from our previous study on women's motivations [24] was not found to be an important factor in this current study.…”
Section: The Women Take the Lead And Filter Informationsupporting
confidence: 89%
See 3 more Smart Citations